ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN BELANJA PADA BADAN KEUANGAN DAN ASET DAERAH KOTA KUPANG - Maria R. A. Nono; Rosmiati Rosmiati; R. Setyo Budi Suharto; Agnes K. B. Mudamakin (JAKA - Jurnal Jurusan Akuntasi, 2020)
This study aims to prove the existence of factors that influence the absorption of the expenditure budget at Badan Keuangan dan Aset Daerah Kota Kupang through filling out a questionnaire for employees at the agency. The focus of this research is on the analysis of factors that influence budget absorption using the aspects of planning documents, human resource factors, and procurement documents.This type of research is causality research, namely a research design designed to examine the possibility of a causal relationship between variables. The data analysis technique used in this research is multiple linear regression with the help of the SPSS 16 programThe results of this study indicate that there is a positive and significant effect of planning documents, human resources (HR), and procurement documents on budget absorption at Badan Keuangan dan Aset Daerah Kota Kupang. The significance level of the planning document variable (0.006) is less than the significant level (0.05); it can be concluded that hypothesis 1 is accepted. The level of significance of the human resources variable (0.025) is less than the significant level (0.05); it can be concluded that hypothesis 2 is accepted. The significance level of the procurement document variable (0.001) is less than the significant level (0.05), it can be concluded that hypothesis 3 is accepted.